Modular mastery of inflammation: umbilical cord mesenchymal stem cells as a therapeutic frontier - Yin, Li; Sun, Chen-yang; Chen, Gui-lai; Xiang, Zhuo; Hu, Bao-quan; Zhou, Fang; Wang, Qiang (Frontiers in Immunology, 2025)
Inflammation operates as a dual-edged sword in physiological defense and pathological damage, driving conditions from diabetes to neurodegeneration. Current anti-inflammatory therapies-NSAIDs, corticosteroids, and biologics-face clinical bottlenecks including non-specific toxicity, therapeutic ceiling effects, and drug resistance. Umbilical cord mesenchymal stem cells (UC-MSCs) emerge as a transformative alternative, leveraging three synergistic modules: Immune reprogramming, Inflammasome inhibition, Intercellular communication. Clinical trials demonstrate efficacy in inflammatory bowel disease, COVID-19 ARDS, and graft-versus-host disease. UC-MSCs outperform conventional therapies by multi-pathway modulation and tissue-regenerative capacity, though challenges persist in cell heterogeneity and long-term safety. Future work must standardize dosing protocols and validate scalable production for clinical translation.